Studied on the kinetics of austenitizing phase transition of 1Cr13 steel - L. Xue; H. Y. Gao; F. D. Wang; G. L. Tan; W. Zhang (Metalurgija, 2024)
The austenitizing of steel plays an important role in improving its properties. Studying the kinetics of austenitizing of steel has certain theoretical significance for practical production. In this article, the Differential scanning calorimetry(DSC) was used to measurement the enthalpy change for the austenitizing process of 1Cr13 steel at different heating rates. The kinetic parameters were obtained based on the data of the enthalpy change for the austenitizing process of 1Cr13 steel. The result is shown that the activation energy of austenitizing process of 1Cr13 steel is dependence of the phase transition fraction. The kinetics mechanism function of the austenitizing process is nucleation and growth model, [–ln(1–α)]2/3. The value of the pre-exponential factors is 8,617*1080s-1.